Moving from the neighborhood to the cellblock: the impact of youth’s neighborhoods on prison misconduct - Boessen, Adam (Crime & delinquency, 2016)
This study examines how prior neighborhood characteristics affect youth’s offending when youths move into an incarceration context. Neighborhood ethnic heterogeneity, residential stability, and disadvantage are often predictive of neighborhood crime, but it is unclear how these neighborhood constructs continue to affect youth’s behavior inside a secure facility. In a sample of recently incarcerated juvenile offenders (N = 320), this study examined how prior neighborhood characteristics affect institutional offending over the first 8 weeks of incarceration. Although disadvantage did not relate to institutional offending, results indicate that youths from racially/ethnically homogenous communities are more likely to offend during the initial weeks of incarceration, whereas youths from residentially stable communities are more likely to offend in the latter weeks.